2011
DOI: 10.1111/j.1475-1305.2009.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fibre Geometry and Volume Fraction on the Flexural Behaviour of Steel‐Fibre Reinforced Concrete

Abstract: This work aims in studying the mechanical behaviour of concrete, reinforced with steel fibres of different geometry and volume fraction. Experiments include compression tests and four‐point bending tests. Slump and air content tests were performed on fresh concrete. The flexural toughness, flexural strength and residual strength factors of the beam specimens were evaluated in accordance with ASTM C1609/C1609M‐05 standard. Improvement in the mechanical properties, in particular the toughness, was observed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(84 citation statements)
references
References 16 publications
6
64
1
2
Order By: Relevance
“…In fact, the tests on samples with a fibre content of 40 kg/m 3 reveal even lower energy dissipation than the ones with 30 kg/m 3 . This is in contradiction to the generally known information that energy dissipation at cracked state increases with a growing fibre content in the matrix, [2][3][4][5][6][7][8][9][10]. Similarly, a higher fibre content (40 kg/m 3 ) for both random and deliberate orientations generates lower fracture energies compared to a lower fibre content (30 kg/m 3 ).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In fact, the tests on samples with a fibre content of 40 kg/m 3 reveal even lower energy dissipation than the ones with 30 kg/m 3 . This is in contradiction to the generally known information that energy dissipation at cracked state increases with a growing fibre content in the matrix, [2][3][4][5][6][7][8][9][10]. Similarly, a higher fibre content (40 kg/m 3 ) for both random and deliberate orientations generates lower fracture energies compared to a lower fibre content (30 kg/m 3 ).…”
Section: Discussioncontrasting
confidence: 52%
“…The parameters with the strongest influence on the improved tensile capacity compared to plain cement or concrete are the fibre mass or volume content (usually expressed in [kg/m 3 ] or [%], respectively), fibre aspect ratio (length-to-diameter-ratio), bond efficiency of the embedded fibre(s), and the fibre orientation with respect to the direction of the applied stress. A higher fibre content and higher aspect ratio generally lead to a higher post cracking strength [2][3][4][5][6][7][8][9][10][11]. On the other hand, the bond characteristics of the embedded fibres are determined by the fibre geometry and surface adhesion [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Compressive tests showed that the fibers in concrete had only a marginal effect on the compressive strength of concrete (Olivito and Zuccarello 2010;Soulioti et al 2011). However, studies on compression behavior of synthetic fiber reinforced concrete is very limited.…”
Section: Behavior Of Frc Under Compression and Flexurementioning
confidence: 99%
“…Furthermore, the increase of the flexural strength of SFRC is significantly improved with increasing the fiber aspect ratio (i.e. fiber length/fiber diameter ratio) and fiber volume fraction [10].…”
Section: Literature Reviewmentioning
confidence: 89%